The genetic and clinical features of cardiac channelopathies. (July 2010) - Roberts, Jason D; Gollob, Michael H
Sudden cardiac death, secondary to malignant ventricular arrhythmias, has traditionally been associated with structural heart disease. An important exception includes a group of clinical entities referred to as 'channelopathies' that develop secondary to genetic mutations, which alter cardiac ion channel activity. Otherwise healthy individuals affected by these forms of primary electrical disease are vulnerable to fatal arrhythmic events from a very young age. At present, there are four distinct conditions that are classified as cardiac channelopathies, namely congenital long-QT syndrome, Brugada syndrome, catecholaminergic polymorphic ventricular tachycardia and short-QT syndrome. Our growing insight into the genetics of these conditions has led to an improved understanding of the molecular pathophysiology responsible for the malignant arrhythmias characterizing these disorders. However, despite our knowledge of these conditions, the success of medical therapy remains modest and the prevention of sudden cardiac death may necessitate insertion of an implantable cardioverter-defibrillator. The young age of affected patients makes this a particularly undesirable treatment strategy and emphasizes the importance of translating our insight into the molecular pathophysiology defining these conditions into more effective forms of therapy.